HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI MENGENAI DAMPAK KEHAMILAN DI USIA REMAJA TERHADAP STATUS KESEHATAN MENTAL DI SMAN 3 LANGGAM - Sari, Silvy Lolinda; Erika, Erika; Rajagukguk, Sartika (Ensiklopedia of Journal, 2025)
Abstract: The impact of teenage pregnancy on mental health can cause them to tend to experience high depression, a sense of hopelessness, difficulty adapting to the community environment, and avoiding things related to pregnancy. Lack of knowledge about reproductive health can encourage negative behaviors that are at risk of causing teenage pregnancy. The purpose of this study was to determine the relationship between knowledge and attitudes of adolescent girls regarding the impact of teenage pregnancy on mental health status at SMAN 3 Langgam. The research design used was quantitative descriptive correlation with a cross sectional approach. The sampling technique used total sampling technique, with the number of respondents 68 people. The research location will be conducted at SMAN 3 Langgam. Data collection tools are questionnaire sheets of knowledge of adolescent girls about the impact of pregnancy, attitudes of adolescent girls about the impact of pregnancy and mental health which are analyzed univariately and bivariately with the Chi-Square test. The results of the study obtained knowledge of adolescent girls 0.006, attitude of adolescent girls 0.000, then there is a relationship between knowledge and attitude of adolescent girls about the impact of pregnancy in adolescence on mental health status in adolescents at SMAN 3 Langgam.  It is expected for schools to make counseling programs for adolescent girls related to teenage pregnancy and adolescent mental health. Keywords: Knowledge, Attitude, Teenage Pregnancy, Mental Health